Comparative study of evaluation of the oral stereognostic ability between diabetic and nondiabetic complete denture wearers with and without denture - Kalarani Gnanasambandam; Suma Karthigeyan; Syed Asharaf Ali; Mohan Govindharajan; Krishna Raj; R Murugan (Wolters Kluwer Medknow Publications, 2019)
Background: The diabetic subjects would have impaired oral stereognostic ability (OSA) compared with normal subjects due to diabetic neuropathy and microcirculatory disturbances. This study was conducted to compare the OSA between diabetic and nondiabetic complete denture wearers with and without denture. Materials and Methods: In this in vivo study the present comparative study comprised of seventy edentulous subjects (36 males and 34 females), aged from 35 to 84 rehabilitated with complete dentures (among them 35 were diabetic and 35 subjects were nondiabetic complete denture wearer). The OSA tests were conducted using acrylic test samples of 12 shaped forms, which were placed in patient's mouth for a given period of time for identification and scored according to three-point scale as OSA score and the identification time was also recorded. The data obtained were analyzed using Chi-square test, t-test, and Pearson's correlation coefficient (P < 0.05). Results: In this study, diabetic complete denture wearers got the mean OSA score of 12.43 ± 3.93 without dentures, which was lower than nondiabetic complete denture wearer group (14.82 ± 4.44). There was a significant difference (P = 0.020*) in the identification of test pieces. Conclusion: Within limitations of this study, diabetic complete denture wearers showed decreased OSA than nondiabetic subjects, particularly it was significant while not wearing dentures. Oral stereognosis may be used as one of the clinical aids in predicting patient's performance to a prosthesis. Based on their response, we can educate the patient about the prognosis.